TODDLERS DEVELOPMENT MONITORING WITH EARLY DETECTION STIMULATION ACTION - Rosa Mutianingsih; Ema Melinda (International Journal of Midwifery Research, 2022)
Repeated and continuous stimulation in every aspect of development means that it has provided opportunities for children to grow and develop optimally. The purpose of this study was to determine the use of early detection stimulation measures on the development of toddlers aged 2-5 years at Karang Taliwang Health Center. The design of this research is descriptive. The population is all toddlers aged 2-5 years who are in the working area of ​​the Karang Taliwang Community Health Center. The instrument of collection used a questionnaire. The analysis used in this research is univariate analysis. From the results of the study, it was shown that 59 (67.8%) stimulation measures were performed with appropriate developments, 24 (27.6%) stimulation measures performed and 4 (4.6%) stimulators were carried out with developmental deviations. ). It is hoped that the results of this study can be used as learning materials to determine the use of early stimulation measures on the development of toddlers aged 2-5 years.